Everolimus Plus Exemestane in Advanced Breast Cancer: Safety Results of the BALLET Study on Patients Previously Treated Without and with Chemotherapy in the Metastatic Setting. (June 2017) - Generali, Daniele; Montemurro, Filippo; Bordonaro, Roberto; Mafodda, Antonino; Romito, Sante; Michelotti, Andrea; Piovano, Pierluigi; Ionta, Maria Teresa; Bighin, Claudia; Sartori, Donata; Frassoldati, Antonio; Cazzaniga, Marina Elena; et al.
Abstract: Background: The BALLET study was an open‐label, multicenter, expanded access study designed to allow treatment with everolimus plus exemestane in postmenopausal women with hormone receptor‐positive metastatic breast cancer progressed following prior endocrine therapy. A post hoc analysis to evaluate if previous chemotherapy in the metastatic setting affects the safety profile of the combination regimen of everolimus and exemestane was conducted on the Italian subset, as it represented the major part of the patients enrolled (54%). Patients and Methods: One thousand one hundred and fifty‐one Italian patients were included in the present post hoc analysis, which focused on two sets of patients: patients who never received chemotherapy in the metastatic setting (36.1%) and patients who received at least one chemotherapy treatment in the metastatic setting (63.9%). Results: One thousand one hundred and sixteen patients (97.0%) prematurely discontinued the study drug, and the main reasons reported were disease progression (39.1%), local reimbursement of everolimus (31.1%), and adverse events (AEs) (16.1%). The median duration of study treatment exposure was 139.5 days for exemestane and 135.0 days for everolimus. At least one AE was experienced by 92.5% of patients. The incidence of everolimus‐related AEs was higher (83.9%) when compared with those that occurred with exemestane (29.1%), and the most commonly reported everolimus‐related AE was stomatitis (51.3%). However, no significant difference in terms of safety related to the combination occurred between patients without and with chemotherapy in the metastatic setting. Conclusion: Real‐life data of the Italian patients BALLET‐related cohort were an adequate setting to state that previous chemotherapy did not affect the safety profile of the combination regimen of everolimus and exemestane. Implications for Practice: With the advent of new targeted agents for advanced or metastatic breast cancer, multiple lines of therapy may be possible, and components of the combined regimens can overlap from one line to another. Thus, it is important to assess even the potential of cumulative and additive toxic effects among the drugs. Previous chemotherapy did not affect the safety profile of the combination regimen of everolimus and exemestane. The continuous monitoring of the safety signals of this drug combination from general clinical practice is important, in particular for stomatitis. Abstract : This study presents results of the BALLET study, which focused on the use of everolimus/exemestane combination in postmenopausal women with ER+ locally advanced or metastatic breast cancer after recurrence or progression after nonsteroidal aromatase inhibitor treatment. Real‐life data of the cohort are reported.